The use of organic fertilizers and biological agents to improve the fertility of degraded Ultisols for enhancing growth of porang (Amorphophallus oncophyllus Prain) - Yusuf, Dewi Nurhayati; Muhidin, Muhidin; Sutariati, Gusti Ayu Kade; Hasid, Rachmawati; Sadimantara, Gusti Ray; Alam, Syamsu (Brawijaya University, 2025)
The study aimed to determine the optimal composition of planting material to enhance the growth of porang seedlings. The study was conducted in the laboratory of the Agronomy Department, Agriculture Faculty of Halu Oleo University, Kendari, and continued in field nursery at Wua-Wua District, Kendari City, Southeast Sulawesi. This research was carried out in two stages: (1) testing at the germination stage in the laboratory and (2) testing at the seedling stage in a field experiment. Kendari City, Southeast Sulawesi, from October to December 2021. Testing at the germination stage in the laboratory used a completely randomized design consisting of six treatments of planting media compositions, namely M0 (soil), M1 (soil + rice husk charcoal; 1;1), M2 (soil + rice husk charcoal + organic fertilizer; 1:2:1), M3 (soil + rice husk charcoal + organic fertilizer; 1:1:2), M4 (soil + rice husk charcoal + organic fertilizer; 1:2:2), M5 (soil + rice husk charcoal + organic fertilizer; 1:2:3). While the test at the nursery stage used a randomized block design, with the same treatments as the treatments at the germination stage. The findings indicated that the composition of planting media significantly affected the growth of porang seedlings. The optimal planting media composition for enhancing the growth of porang seedlings consisted of soil, rice husk charcoal, and organic fertilizer in a ratio of 1:2:3. The increase in plant growth, as indicated by stem diameter, was 133% relative to the control group.